1997
DOI: 10.1007/s002770050319
|View full text |Cite
|
Sign up to set email alerts
|

Absence of mutations in the RET gene in acute myeloid leukemia

Abstract: Expression of the tyrosine kinase receptor RET has previously been detected in normal hematopoietic cells, and especially in cells of the myeloid lineage. Furthermore, RET was shown to be differentially expressed in acute myeloid leukemia (AML), a disease characterized by excessive cell growth and aberrant maturation of cells, with the highest levels of expression in leukemias with monocytic differentiation. RET is known to be expressed in cells from the excretory system and from the developing central and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
4
12
0
Order By: Relevance
“…Somatic and germ-line RET mutations leading to gene activation are responsible for several human diseases, including multiple endocrine neoplasia types 2A and 2B and papillary thyroid carcinomas (24). Nevertheless, mutations of RET as a mechanism of overexpression were discarded in the present MYST3-CREBBP series, in accordance with a previous study analyzing diverse AML subtypes (33). One of the most striking findings of this study was the similarities observed between MYST3-CREBBP and MLL-rearranged leukemias.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Somatic and germ-line RET mutations leading to gene activation are responsible for several human diseases, including multiple endocrine neoplasia types 2A and 2B and papillary thyroid carcinomas (24). Nevertheless, mutations of RET as a mechanism of overexpression were discarded in the present MYST3-CREBBP series, in accordance with a previous study analyzing diverse AML subtypes (33). One of the most striking findings of this study was the similarities observed between MYST3-CREBBP and MLL-rearranged leukemias.…”
Section: Discussionsupporting
confidence: 84%
“…Thus, genes such as PRL, C20orf103, RET, GGA2, ICSBP1, ITGA7, DAP, IRAK1, and PPARG were overexpressed almost exclusively in MYST3-CREBBP cases. Among those genes, PRL and RET have been occasionally reported to be involved in leukemogenesis (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). In this regard, an increased expression of prolactin protein in blast populations has been observed in anecdotal cases of monocytic-lineage leukemia as well as in the eosinophilic cell line Eol-1 (25)(26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the coexpression, demonstrated here, by RETexpressing leukaemic cells of specific adhesion molecules capable to mediate interactions of myeloid blasts with the bone marrow microenvironment (Bradstock & Gottlieb, 1995) may represent additional mechanism(s) favouring the 'physiological' cross-talk of RET, as expressed by AML blasts, with GDNF and GDNFR-a, in turn provided by stromal and accessory cells. Such a model is in agreement with a recent finding that no RET gene structural aberrations and activating mutations can be found in AMLs (Visser et al, 1997). Interestingly, this seems to be in apparent contrast with the high rate of activating point mutation of the RET gene found in other non-haemopoietic malignancies (Eng, 1996), but is consistent with the overall absence of functionally active point mutations of other haemopoietic RTKs, including C-KIT and C-FMS in AMLs (Springall et al, 1993;Arland et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…A similar result was found in AML where the structure of RET was investigated by Southern blot and denaturing gradient gel electrophoresis in 17 patients. 22 The two RET fusion genes described here merge exon 12 of RET in 3 0 with BCR exon 4 or FGFR1OP exon 12 in 5 0 . The 5 0 part of the fusion genes encodes dimerization domains, in a similar way to all the fusion gene partners reported in papillary thyroid, lung and colorectal carcinomas associated with RET rearrangements (PTC1…”
Section: Discussionmentioning
confidence: 90%